Murach's Oracle SQL & PL/SQL: works with all versions through 11g - Murach, Joel (Training & reference, 2008)
If you are developing applications that access Oracle databases, you can save time and work by having SQL do more of the data handling for you - this book shows you how. It teaches you how to create effective SQL queries to extract and update the data in an Oracle database.